A büntetéskiszabási szemlélet alakulása – a büntető kódex folyamatos módosításának tükrében - Hati, Csilla (Debreceni Jogi Műhely, 2012)
The criminal code has had a number of essential revisions during the past years, which has received distinct viewpoints concerning the improvement of punishments from the judiciary in criminal cases. The reasons of modifications can be explained mainly by the different penalty politics coming into prominence, occasionally having respect for different social approaches. It is periodically distinct which activities are indictable offences, which of the punishments serve the prevention of committing an act of crime the best in the fight against criminality. It is interesting to study how these sweeping changes can appear and effect in the daily legal activities. How far can the changes lobby the judges and prosecutors? Which punishment is ideal in the case - suiting to the aim of punishment – in the interest of the protection of society? As a result, analyzing judgments and interviewing some professional jurists (as far as I can) the different requirementson infliction of punishments do not appear immediately in practice and do not appear in the similar way concerning the functions of judges and prosecutors. It is not machines that pass judgement in a case, which could modify the expectation concerning the result.